Validation of the tablet-administered Brief Assessment of Cognition (BAC App) - Atkins, Alexandra S.; Tseng, Tina; Vaughan, Adam; Twamley, Elizabeth W.; Harvey, Philip; Patterson, Thomas; Narasimhan, Meera; Keefe, Richard S.E. (Schizophrenia research, 2017)
Computerized tests benefit from automated scoring procedures and standardized administration instructions. These methods can reduce the potential for rater error. However, especially in patients with severe mental illnesses, the equivalency of traditional and tablet-based tests cannot be assumed. The Brief Assessment of Cognition in Schizophrenia (BACS) is a pen-and-paper cognitive assessment tool that has been used in hundreds of research studies and clinical trials, and has normative data available for generating age- and gender-corrected standardized scores. A tablet-based version of the BACS called the BAC App has been developed. This study compared performance on the BACS and the BAC App in patients with schizophrenia and healthy controls. Test equivalency was assessed, and the applicability of paper-based normative data was evaluated. Results demonstrated the distributions of standardized composite scores for the tablet-based BAC App and the pen-and-paper BACS were indistinguishable, and the between-methods mean differences were not statistically significant. The discrimination between patients and controls was similarly robust. The between-methods correlations for individual measures in patients were r>0.70 for most subtests. When data from the Token Motor Test was omitted, the between-methods correlation of composite scores was r=0.88 (df=48; p<0.001) in healthy controls and r=0.89 (df=46; p<0.001) in patients, consistent with the test-retest reliability of each measure. Taken together, results indicate that the tablet-based BAC App generates results consistent with the traditional pen-and-paper BACS, and support the notion that the BAC App is appropriate for use in clinical trials and clinical practice.